The Role of the Phase of QBO in Modulating the Influence of the SSW Effect on the Equatorial Ionosphere. Issue 7 (13th July 2019) - Yadav, Sneha; Vineeth, C.; Kumar, K. K.; Choudhary, R. K.; Pant, T. K.; Sunda, S.
Abstract: This study investigates the role of stratospheric quasi‐biennial oscillation (QBO) in modulating the response of equatorial/low‐latitude ionosphere over the Indian sector to the major sudden stratospheric warmings (SSWs) occurred during the period 2003 to 2013. The analysis based on the equatorial electrojet‐induced surface magnetic field, total electron content, and mesospheric wind data reveals that the equatorial ionosphere responds in distinctly different ways to the SSWs occurred during different QBO phases. The peaking time of the equatorial electrojet and occurrence time of counter electrojet displays a shift toward morning/evening sector during the westward/eastward phase of the QBO as inferred from the zonal mean zonal wind at 10‐hPa level ( 30 km). The analysis reveals that the enhancement and depletions seen in total electron content over both the equatorial and low‐latitude ionosphere display a shift toward morning/evening during the westward/eastward phase of the QBO. The upper mesospheric tides (diurnal and semidiurnal) estimated using the meteor radar measured winds over the dip equator also exhibit similar shift in their phases. The occurrence of periodic counter electrojets during the SSW period is found to be coinciding with enhancement in polar stratospheric temperature and in close association with the increased amplitude of the semidiurnal tide. These observations clearly vindicate that the phase of the QBO plays a crucial role in structuring the equatorial electrodynamics and electron density distribution over the low‐latitudes during the SSW events. Key Points: Prevailing phase of the QBO was found to be influencing the response of equatorial ionosphere prior‐to and during the SSW events The occurrence of periodic CEJs was found to be shifting toward morning (evening) during the westward (eastward) phase of the QBO The phase of the upper mesospheric tides (diurnal and semidiurnal) over the dip equator and time variation of the TEC over equatorial and low latitudes also revealed a similar pattern